Do income levels affect the food consumption pattern of households? Evidence from Indonesia - Baladina, Nur; Toiba, Hery; Hanani, Nuhfil; Suhartini, Suhartini; Widarjono, Agus (Asian Economic and Financial Review, 2024)
Prior studies have proven that income significantly affects household food consumption patterns. However, there is little research on the impact of different income levels on household food demand in Indonesia. This research aims to estimate the elasticity of household food demand at different income levels using the Quadratic Almost Ideal Demand System (QUAIDS) model with a two-step budgeting estimation approach. The data is from the Indonesian National Socio-Economic Survey (SUSENAS) 2020, which surveyed 328,801 households. The findings indicate that the income level of households has a significant effect on household demand for carbohydrate and animal protein source foods. The lowest- and low-income households have the highest proportion of food expenditure. However, in absolute terms, their expenditure on food is the lowest. All commodities exhibit positive expenditure elasticity and negative own-price elasticity across all income levels. The consumption of rice, fish, and chicken are more responsive to policies aimed at increasing household income. Conversely, the consumption of corn, flour, cassava, beef, and eggs are more responsive to price control policies. It is crucial for food policy in Indonesia to prioritize the needs of the lowest- and low-income households, ensuring that they have access to improved food consumption patterns.